Asthma and allergies in a cohort of adolescents conceived with ART. Issue 6 (December 2022) - Wijs, Laura A.; Doherty, Dorota A.; Keelan, Jeffrey A.; Penova-Veselinovic, Blagica; Burton, Peter; Yovich, John L.; Hall, Graham L.; Sly, Peter D.; Holt, Patrick G.; Hart, Roger J.
Highlights: No difference in the prevalence of current asthma in ART versus non-ART adolescents Lower prevalence of bronchial hyperresponsiveness in ART versus non-ART adolescents Slightly altered lung function in ART versus non-ART adolescents Higher prevalence of allergies in ART versus non-ART adolescents Abstract: Research question: Are asthma and allergies more common in adolescents conceived with assisted reproductive technologies (ART) compared with adolescents conceived without? Design: The Growing Up Healthy Study (GUHS) is a prospective cohort study including ART-conceived offspring born between 1991 and 2001 in Perth, Australia. Their long-term health outcomes, including asthma and allergy parameters, were compared with those of their counterparts conceived without ART from the Raine Study Generation 2 (Gen2), born in 1989–1991. At age 14, 152 GUHS and 1845 Gen2 participants completed the following assessments: the International Studies of Asthma and Allergies in Childhood (ISAAC) questionnaire, spirometry, methacholine challenge testing and skin prick testing (SPT). Results: No differences were detected in the prevalence of current asthma (7.7% versus 10.8%, adjusted odds ratio [aOR] 0.82 (95% CI 0.44–1.52), P  = 0.530). Spirometry-measured lung volumes were larger in the ART adolescents. Bronchial hyperresponsiveness was less prevalent in the ART cohort (8.8 versus 18.6%, P  = 0.006). Current allergic rhinoconjunctivitis (ARC) rates were significantly higher in the ART cohort (32.4% versus 25.2%, aOR 1.52 [95% CI 1.03–2.26], P  = 0.036), with no cohort differences in atopic dermatitis. Food allergies were more prevalent in the ART cohort (20.7 versus 10.9%, aOR 1.89 [95% CI 1.17–3.06], P  = 0.010) with more adolescents having a positive SPT (68.0% versus 45.4%, aOR 3.03 [95% 1.99–4.63], P < 0.001). Conclusions: This study reports no differences in asthma prevalence, slightly altered lung function, an increase in ARC, food allergies and positive SPT in the ART-conceived adolescents. These findings are important to families and healthcare providers and may open up possibilities for targeted screening and treatment. Further studies are required to confirm these findings.